Deafferentation-Induced Plasticity of Visual Callosal Connections: Predicting Critical Periods and Analyzing Cortical Abnormalities Using Diffusion Tensor Imaging - Jaime F. Olavarria; Andrew S. Bock; Lindsey A. Leigland; Christopher D. Kroenke (Neural Plasticity)
Callosal connections form elaborate patterns that bear close association with striate and extrastriate visual areas. Although it is known that retinal input is required for normal callosal development, there is little information regarding the period during which the retina is critically needed and whether this period correlates with the same developmental stage across species. Here we review the timing of this critical period, identified in rodents and ferrets by the effects that timed enucleations have on mature callosal connections, and compare it to other developmental milestones in these species. Subsequently, we compare these events to diffusion tensor imaging (DTI) measurements of water diffusion anisotropy within developing cerebral cortex. We observed that the relationship between the timing of the critical period and the DTI-characterized developmental trajectory is strikingly similar in rodents and ferrets, which opens the possibility of using cortical DTI trajectories for predicting the critical period in species, such as humans, in which this period likely occurs prenatally. Last, we discuss the potential of utilizing DTI to distinguish normal from abnormal cerebral cortical development, both within the context of aberrant connectivity induced by early retinal deafferentation, and more generally as a potential tool for detecting abnormalities associated with neurodevelopmental disorders.